Persepsi Masyarakat Kelurahan Ogan Baru terhadap Kebijakan Vaksinasi Covid-19 Tahun 2021 - Melinda, Sandra; Kencana, Novia; Amaliatulwalidain, Amaliatulwalidain (Jurnal Publisitas, 2022)
The Covid-19 Vaccination Policy is a policy issued by the Government after the outbreak of an infectious disease that attacked Indonesia, namely the Coronavirus Disease with the issuance of Law Number 4 of 1984 concerning Outbreaks of Infectious Diseases (State Gazette of the Republic of Indonesia of 1984 Number 20, Supplement to the State Gazette of the Republic of Indonesia Number 3237). The purpose of this study is to find out how the Ogan Baru Village Community Perceptions of the Covid-19 Vaccination Policy in 2021. The method used is a qualitative method by looking at the phenomenon more clearly and in depth according to what is happening and developing in social situations. The data collection used is Observation, Interview, Questionnaire or Questionnaire and Documentation. Using Bimo Walgito's Perception theory, the results of this study show that the community's perception of the new Ogan Village towards the 2021 Covid-19 Vaccination Policy is good enough, this can be seen from the knowledge of the community where many people already know about the covid-19 vaccination, public acceptance has been many agree with the implementation of the covid-19 vaccination, it's just that there are obstacles in the implementation of the vaccination, namely public trust in the content in the halal vaccine or not for use.